(untitled) (Journal of Medical Sciences, 2022)
Stroke is an important cause of disability among adults and is one of the leading causes of death worldwide. Stroke is a term used to describe an abrupt-onset focal neurologic deficit that lasts at least 24 hours and is of presumed vascular origin[1]. Stroke can be either ischemic or hemorrhagic (88% and 12% respectively, of all strokes in the 2003 American Heart Association report[2], Risk factors for stroke can be subdivided into non-modifiable and modifiable[3]. Aim: this study aims to investigate community knowledge about stroke and its risk factors. Method and Procedures: A cross-sectional observational study was conducted in polyclinics located in Benghazi between November to January 2017-2018. Once before the interview, participants were asked to verbal consent to participate in the study. Participants were interviewed using pre-piloted questionnaire and their history of their morbidity and their lifestyle. Results During the study period, a total of 229 people, the response rate was (93%). The majority was in the younger age group between (18-29-year-old) found 84 (37%), female 153 (67%) and high education people 138(60%). In current study the information source most of friends 90 (40%), less percentage internet 23 (10%) and work shop 23 (10%). Conclusion: The current study shows that the most of participants can define the disease but their knowledge about its risk factors and dangerous signs were not enough. Almost of participants depend on their friends as source of information.